Visualisasi Garap Gerak dan Karakter dalam Tari Wireng di Mangkunegaran - Hadi Subagyo (Institut Seni Indonesia Surakarta, 2010)
The performance of the wireng dance genre is the manifestation of the entirety of a system which is a complexity of treatment of various visual components. The visual treatment of movement and character is the main component of the wireng genre. The treatment of movement and character, which includes the qualities of the movement and character of the strong male dance, refined male dance, and female dance styles in the wireng dance, displays a wealth of vocabulary, technique, and form. In addition, the aesthetical values contained in the dance create an impression which enriches the spiritual experience of the audience. The visual treatment of movement and character also contains an important and serious message for the life and developmentof the wireng dance in the Mangkunegaran Palace. Keywords : Wireng dance, treatment, movement and character.